Thinking about thinking : metacognition for music learning - Benton, Carol W., 1950- (Lanham : Rowman & Littlefield, 2014)
This book provides music educators with information, inspiration, and practical suggestions for teaching music. Written for music educators in multiple content areas and grade levels, the book sets forth guidelines for promoting the use of metacognitive skills among music students. Along with presenting an extensive overview of research on the topic, this book shows how ideas gleaned from research can be put into daily practice in music classrooms and studios. General music teachers, directors of choral and instrumental ensembles, applied music teachers, future music educators, and music education collegiate faculty will find useful ideas and information here. In the current educational climate where all teachers are required to demonstrate that they encourage higher order thinking among their students, this book gives music educators the tools they need to accomplish the task.
Thinking about thinking : what is metacognition? -- Metacognition for music learning -- Metacognition and self-regulation for music learning -- Metacognition and self-reflection for music learning -- Metacognition and self-evaluation for music learning -- Socially shared metacognition : thinking aloud for music learning -- Metacognition for independent music practice sessions -- What can teachers do?
"Published in partnership with NAfME: National Association for Music Education"
Includes bibliographical references (pages 153-163)
Keywords: Music -- Instruction and study; Metacognition